Achieving Control of Asthma in Children in Africa (ACACIA): protocol of an observational study of children's lung health in six sub-Saharan African countries. Issue 3 (18th March 2020) - Mosler, Gioia; Oyenuga, Victoria; Addo-Yobo, Emmanuel; Adeyeye, Olayinka Olufunke; Masekela, Refiloe; Mujuru, Hilda Angela; Nantanda, Rebecca; Rylance, Sarah; Ticklay, Ismail; Grigg, Jonathan
Abstract : Introduction: Little is known about asthma control in the rising number of African children who suffer from this condition. The Achieving Control of Asthma in Children in Africa (ACACIA) study is an observational study collecting evidence about paediatric asthma in urban areas of Ghana, Malawi, Nigeria, South Africa, Uganda and Zimbabwe. The primary objectives are: (1) to identify 3000 children aged between 12 years and 14 years with asthma symptoms; and (2) to assess their asthma control, current treatment, knowledge of and attitudes to asthma and barriers to achieving good control. Secondary objective is to develop interventions addressing identified barriers to good symptom control. Methods and analysis: Each centre will undertake screening to identify 500 school children with asthma symptoms using questions from the Global Asthma Network's questionnaire. Children identified to have asthma symptoms will fill in a digital survey, including: Asthma Control Test, questions on medication usage and adherence, medical care, the Brief-Illness Perception questionnaire and environmental factors. Exhaled nitric oxide testing and prebronchodilator and postbronchodilator spirometry will be performed. A subgroup of children will participate in focus group discussions. Results will be analysed using descriptive statistics and comparative analysis. Informed by these results, we will assess the feasibility of potential interventions, including the adaption of a UK-based theatre performance about asthma attitudes and digital solutions to improve asthma management. Ethics and dissemination: The ACACIA study has been reviewed by the Queen Mary University of London Ethics of Research Committee in the UK. All African centres have received local ethical approval for this study. Study results will be published in academic journals and at conferences. Study outputs will be communicated to the public via newsfeeds on the ACACIA website and Twitter, and through news media outlets and other local dissemination. Trial registration number: 269211.